Relationship between body mass index and quality of life, use of dietary and physical activity self-management strategies, and mental health in individuals with polycystic ovary syndrome - Masters Melissa; Grevstad Nels (Open Health)
Polycystic ovary syndrome (PCOS) can negatively affect health and well-being. This study aimed to assess quality of life, use of self-management strategies, stress, anxiety, and depression in people with PCOS, and the effect of body mass index (BMI) on these factors. An online survey was distributed on PCOS social media sites and email listservs. Categorical data were analyzed as counts and percentages. Relationships between BMI and scores for PCOS quality of life (PCOSQ), use of diet and physical activity self-management strategies, perceived stress scale, and hospital anxiety and depression scale were analyzed using simple linear regression analyses. Significance was set at p < 0.05. The median BMI of participants (n = 101) was 33.12 kg/m2. PCOSQ scores were similar across BMI groups for many domains. Linear regression analyses revealed that BMI predicted variation in weight and hirsutism scores. Self-management scores were low for all BMI groups. Linear regression analyses revealed no significant relationships between BMI and scores for self-management strategy categories. Most participants had moderate stress (n = 55, 59.8%), abnormal anxiety (n = 50, 56.2%), and normal depression (n = 48, 53.9%) levels. Linear regression analyses revealed no significant relationships between BMI and these scores. Individuals of all body sizes with PCOS may experience quality of life disruptions and mental health concerns and may utilize dietary and physical activity self-management strategies at a low level. In PCOS, quality of life and mental health concerns should be assessed, in addition to metabolic impacts, and an individualized approach to increasing the use of self-management strategies should be implemented.